1184. Activity of anti-pseudomonal antibiotics among all Pseudomonas aeruginosa (PSA) at an academic medical health system, including β-lactam, multi-drug (MDR) and extensively drug resistant (XDR) strains. (31st December 2020) - Rose, Warren; Heikkinen, Benjamin; Radaatz, Janet; Puzniak, Laura A; Dillon, Ryan J; Schulz, Lucas
Abstract: Background: PSA with MDR and XDR are a growing threat, and appropriate initial treatment of this organism is critical. C/T is a novel antibiotic with broad gram-negative in vitro susceptibility among surveillance studies. However comprehensive susceptibility analyses of C/T among PSA clinical isolates in comparison with other anti-PSA antibiotics remain limited, since routine clinical C/T susceptibility testing is not typically performed. Methods: This study assessed all adult inpatient cultures positive for PSA from 32 months at an academic health system. Antimicrobial susceptibility was prospectively performed using Kirby Bower disk diffusion and interpreted by BIOMIC V3 during routine clinical care. Initial susceptibility testing included C/T along with amikacin, aztreonam, cefepime, ciprofloxacin, doripenem, gentamicin, imipenem, meropenem, piperacillin/tazobactam, and tobramycin. MDR and XDR isolates were identified using established definitions. The primary outcome was to quantify C/T resistant PSA (includes intermediate and resistant strains). Secondary outcomes were to determine resistance to other anti-PSA antibiotics and to identify C/T activity among isolates with MDR, XDR and pan-β-lactam resistance (PBLR = all β-lactams except C/T). Results: A total of 2990 PSA isolates from 2339 cultures in 1311 individual patients were collected. Most cultures were from the lung (45%), followed by urine (30%), and body fluids (10%). For the primary outcome, 121/2990 (4%) of PSA isolates were C/T resistant. All PSA blood cultures were susceptible to C/T. Table 1 summarizes in vitro activity of all anti-PSA agents evaluated. C/T had the greatest percent susceptibility across all culture locations including MDR/XDR PSA isolates with median MICs of 8 µg/mL. For PBLR strains 35/66 (53%) were susceptible to C/T with a median MIC of 8 µg/mL. Table 1 Conclusion: C/T susceptibility testing during routine care over a 2.5-year period revealed 96% susceptibility among PSA. C/T showed the highest susceptibility among all anti-PSA antibiotics for all culture locations and for MDR and XDR isolates. Given the high rates of resistance to traditional anti-PSA agents, the value of new agents with high rates of in vitro susceptibility in the gram-negative armamentarium is high. Disclosures: Warren Rose, PharmD, MPH, Merck (Grant/Research Support)Paratek (Grant/Research Support) Janet Radaatz, PharmD, Merck (Employee) Laura A. Puzniak, PhD, Merck (Employee) Ryan J. Dillon, MSc, Merck & Co., Inc., (Employee)